Mechanical Behaviour of Fly Ash Reinforced Aluminum Composite Prepared by Casting - Sharma, Venktesh; Akhai, Shalom (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Fly ash is a waste residual material generated by coal burning in thermal power plants, steel plants etc.; its hazard is no less than that so utilizing fly ash in engineering applications is a service to society. Thus developing Aluminum-fly ash composites holds great ground. The current project studies indicate that the values of compressive strength, tensile strength, hardness and wear resistance are improved with the addition of fly ash when the fly ash content is added from 0 % to 20 % replacement by weight of aluminum. How to cite this article: Sharma V, Akhai S. Mechanical Behaviour of Fly Ash Reinforced Aluminum Composite Prepared by Casting. J Adv Res Mech Engi Tech 2019; 6(1&2): 23-26.